Prevalence and associated factors of common mental disorders among internally displaced people by armed conflict in Cabo Delgado, Mozambique: a cross-sectional community-based study - Manafe, Naisa; Ismael-Mulungo, Hamida; Ponda, Fábio; Dos Santos, Palmira F.; Mandlate, Flávio; Cumbe, Vasco F. J.; Mocumbi, Ana Olga; Oliveira Martins, Maria R. (Frontiers in Public Health, 2024)
Background Humanitarian emergencies are a major global health challenge with the potential to have a profound impact on people’s mental and psychological health. Displacement is a traumatic event that disrupts families and affects physical and psychological health at all ages. A person may endure or witness a traumatic incident, such as being exposed to war, and, as a result, develop post-traumatic stress disorder (PTSD). There is a lack of information about post-traumatic stress disorder, depression, and anxiety disorder in low and middle-income countries in humanitarian emergency contexts such as Mozambique. This study aimed to assess the prevalence of PTSD, depression, and anxiety, and associated factors among armed conflict survivors in Cabo Delgado, north region of Mozambique in 2023. Methods A community-based cross-sectional study was conducted between January and April 2023 among 750 participants, who were selected by convenience. A face-to-face interview used the Primary Care Post-Traumatic Stress Disorder Checklist (PC-PTSD-5) to evaluate PTSD, the Generalized Anxiety Disorder Scale (GAD-7) to evaluate anxiety and the Patient Health Questionnaire – Mozambique (PHQ-9 MZ) to evaluate depression. The association between PTSD and demographic and psychosocial characteristics was analyzed using bivariate and multivariable binary logistic regression. We used a 5% significance level. Results The three mental disorders assessed were highly prevalent in our sample with 74.3% PTSD, 63.8% depression, and 40.0% anxiety. The chance of developing PTSD was higher in females (AOR = 2.30, 95% CI 1.50–3.51), in patients with depression symptoms (AOR = 8.27, 95% CI = 4.97–13.74) and anxiety symptoms (AOR = 1.45, 95% CI = 0.84–2.50). Conclusion This study reported that the prevalence of PTSD, depression, and anxiety were high. Patients having depressive symptoms, anxiety symptoms, and being female are more at risk of developing PTSD. There is a need to integrate screening for common mental disorders in the context of humanitarian emergencies and its adapted integration of psychosocial interventions.